INTERACTIONS BETWEEN THE MOTIFS OF WESTERN AND EASTERN PHILOSOPHIES IN THE WORKS BY IVAN KARPENKO-KARYI - Науменко, Н. (Київський національний університет імені Тараса Шевченка, 2021)
The author of this article investigated the interactions between the conceits of Occidental and Oriental (Hindu, first of all) philosophies in the play ‘Khazyayin' (The Master) by Ivan Karpenko-Karyi from the viewpoint of culturological analysis. The ways to interpret the Western paradigm of the writer's reading were correlated to their hypothetical typological coincidences with Hindu motifs, plots, maxims and realities as the constituents of the play's artistic world (including the speech and behavior of the characters, their natural and material environment). Therefore, the correlations between the motifs of various philosophies were confirmed as the displays of the writer's dialogue with Occidental and Oriental cultures on the archetypal level, which is the interpretation of initial philosophical images in their symbolic combinations and, thenceforth, the establishment of their new connotations on Ukrainian cultural background. There was shown that Karpenko-Karyi's characters set up their own rules of behavior – either for each other or for themselves – which absorb the probable archetypal intentions from West as well as from East. As the matter of fact, the actualization of key maxims and aphorisms of different philosophies (both European and Asian) is apparent in the characters' appearance and speech. Particularly, it can be epitomized by the figure of Ivan Kalynovych, the teacher, in whose vital philosophy had been quite unexpectedly revealed the Four Noble Truths of Buddhism (the truth of suffering; the truth of the cause of suffering; the truth of the end of suffering; the truth of the path that leads to the end of suffering). On the other hand, the figure of Terentiy Puzyr in Karpenko-Karyi's comedy is precedent as the collective image of a tyrant described by both Western and Eastern thinkers, considering not only his characteristic appearance (an Ayurvedic Kap'a-type), but also his reluctance to practice what he preached.

З позицій культурологічного аналізу простежено взаємодію концептів західної та східної (передусім ведичної) філософії у творі Івана Карпенка- Карого "Хазяїн". Шляхи інтерпретації західної парадигми філософічної лектури письменника досліджено паралельно з їхніми гіпотетичними типологічними збігами зі східними мотивами, сюжетами, максимами і реаліями як складниками художнього світу п'єси (мовою та поведінкою персонажів, їхнім природним і речовим оточенням). Відтак кореляції мотивів різних філософій утверджено як вияви діалогу автора зі східною та західною культурою на архетипному рівні – через осмислення філософем у їхній символічній сув'язі та надання їм нових конотацій на українському ґрунті.
ВЗАЄМОДІЯ ЕЛЕМЕНТІВ ЗАХІДНОЇ ТА СХІДНОЇ ФІЛОСОФІЙ У ТВОРЧОСТІ ІВАНА КАРПЕНКА-КАРОГО
Keywords: works by I. Karpenko-Karyi; Occidental philosophy; Oriental philosophy; comedy; motif; symbol; interpretation; творчість І. Карпенка-Карого; західна філософія; східна філософія; комедія; мотив; символ; інтерпретація